The power of functional foods as a key role in controlling body inflammation in obesity: a review (Research, Society and Development, 2025)
Introduction: Excess body fat is directly linked to the development of chronic noncommunicable diseases (NCDs), such as type 2 diabetes mellitus, systemic arterial hypertension, and metabolic syndrome. Obesity is considered a chronic, inflammatory, and multifactorial disease that affects both adults and children, requiring ongoing monitoring and treatment. In this context, adopting appropriate nutritional strategies is essential, with functional foods standing out as allies in reducing inflammation and improving the metabolic profile. Objective: To investigate the effectiveness of functional foods as a nutritional strategy in combating obesity and associated inflammation, through a bibliographic survey of specialized literature. Method: This is a narrative review of the literature, original and review scientific articles were selected in the time interval between the years 2015 and 2025. Obtained through research in the main electronic and open access databases: PUBMED, SCIELO, LILACS. Results: Some studies have shown that functional foods (fiber, omega-3s, flavonoids) play an important role in modulating the inflammatory response and oxidizing excess fat in adipose tissue. Regularly including these foods in the diet has shown a positive impact on preventing and controlling complications associated with obesity. Conclusion: Given the above, it is understood that the use of functional foods represents an effective approach in the nutritional treatment of obesity, acting to reduce inflammation and improve metabolic parameters.